Genistein synergizes centchroman action in human breast cancer cells - Kaushik, Shweta (Indian J Pharmacol, 2016)
OBJECTIVES: Despite the progress in the diagnosis and treatment of breast cancer, it remains a major health problem in women. Natural flavones along with chemotherapeutic agents enhance therapeutic response and minimize toxicity of chemical agents. Centchroman (CC) colloquially called as ormeloxifene, is a nonsteroidal oral contraceptive categorized as selective estrogen receptor modulator with anti-breast cancer activity. Genistein (GN), an isoflavone found mainly in soy products possesses anti-cancerous potential against a number of cancers including breast. The present study aims at investigating the combination of CC and GN in human breast cancer cell lines (HBCCs). MATERIALS AND METHODS: Cytotoxic effect of CC and GN separately and in combination were assessed by sulforhodamine B (SRB) assay in MDA MB-231, MDA MB-468, MCF-7, T-47D HBCCs, and nontumorigenic human mammary epithelial cell (HMEC) MCF-10A. The drug interaction was analyzed using CompuSyn software through which combination index and dose reduction index were generated. RESULTS: Combination of CC plus GN exerts significantly higher cytotoxicity compared to each drug per se in HBCCs, whereas HMEC-MCF-10A remains unaffected. CONCLUSION: On an overall basis, the drugs in combination enhanced cell killing in malignant cells. Therefore, the combination of CC with GN may offer a novel approach for the breast cancer.